Analysis of the Effect of Tax Sanctions and Tax Knowledge on Taxpayer Compliance Post-Tax Amnesty at the Medan Polonia Pratama Tax Office - Ina Sally (Journal of Research in Business, Economics, and Education, 2020)
This study aims to discuss the effect of tax sanctions and taxpayer knowledge on taxpayer compliance after tax amnesty. Tax sanctions raise awareness and compliance with legal provisions and obligations. This study aims to re-examine the factors that influence taxpayer compliance. The variables used are tax sanctions and taxpayer knowledge which is hypothesized to affect taxpayer compliance. This study uses multiple regression methods. The sample of this research is 200 people. The level of taxpayer compliance, which is included in the high category, can be reflected and shaped by indicators of compliance, implementation of sanctions, and understanding. The strength of tax sanctions does not have a significant effect on the level of taxpayer compliance.